Novel findings in neutrophil biology and their impact on cardiovascular disease. Issue 8 (27th March 2019) - Bonaventura, Aldo; Montecucco, Fabrizio; Dallegri, Franco; Carbone, Federico; Lüscher, Thomas F; Camici, Giovanni G; Liberale, Luca
Abstract: Neutrophils are the most abundant circulating leucocytes in healthy humans. These cells are central players during acute inflammatory responses, although a growing body of evidence supports a crucial role in chronic inflammation and chemokines and cytokines related to it as well. Thus, both humoral and cellular components are involved in the development of plaque formation and atherosclerosis. Accordingly, CANTOS trial using an interleukin-1 beta antibody confirmed that inflammatory cytokines contribute to the occurrence of myocardial infarction and cardiac death independent of changes in lipids. Recent data revealed that neutrophils are a heterogeneous population with different subsets and functional characteristics (i.e. CD177 + cells, OLFM4 + neutrophils, proangiogenic neutrophils, neutrophils undergoing reverse migration, and aged neutrophils). Importantly, neutrophils are able to synthesize de novo proteins. Neutrophil extracellular trap generation and NETosis have been considered as very important weapons in sterile inflammation. Neutrophil-derived microvesicles represent another mechanism by which neutrophils amplify inflammatory processes, being found at high levels both at the site of injury and in the bloodstream. Finally, neutrophil aging can influence their functions also in relation with host age. These recent acquisitions in the field of neutrophil biology might pave the way for new therapeutic targets to prevent or even treat patients experiencing cardiovascular (CV) diseases. Here, we discuss novel findings in neutrophil biology, their impact on CV and cerebrovascular diseases, and the potential implementation of these notions into daily clinical practice.